The Frugal Innovation Paradox in MSMEs New Product Development - Roymon Panjaitan; Febrianur Ibnu Fitroh Sukono Putra (Jurnal Publikasi Ilmu Manajemen, 2026)
This study examined the influence of entrepreneurial orientation (EO) on new product development (NPD) among MSMEs in Central Java, Indonesia. Furthermore, this research investigated the mediating function of network process quality (NPQ) and the moderating role of frugal innovation (FI) in the relationship between EO and NPD. The data were obtained from 227 MSME owners and managers through a structured questionnaire and subsequently analyzed using partial least squares structural equation modeling (PLS-SEM). The findings revealed that entrepreneurial orientation (EO) significantly contributed to both new product development (NPD) and network process quality (NPQ). FI also has a positive direct effect on NPD, while NPQ positively affects NPD and mediates the relationship between EO and NPD. However, the interaction effect between EO and FI was statistically significant but negative, suggesting that stronger frugal innovation orientation reduced the extent to which entrepreneurial orientation translated into new product development outcomes. These findings indicate that although entrepreneurial orientation encourages opportunity recognition, proactive behavior, and product-related initiatives, excessive emphasis on frugal innovation may limit experimentation and reduce the transformation of entrepreneurial actions into broader new product development outcomes. The study underwrites to the SME innovation literature by showing that frugal innovation is not always an amplifier of entrepreneurial orientation. Instead, under resource-constrained conditions, frugal innovation may function as a strategic boundary condition that limits the marginal impact of EO on NPD.